Digital health transformation in Saudi Arabia: A cross-sectional analysis using Healthcare Information and Management Systems Society' digital health indicators. (August 2022) - Al-Kahtani, Nouf; Alrawiai, Sumaiah; Al-Zahrani, Bnan Mohammed; Abumadini, Rahaf Ali; Aljaffary, Afnan; Hariri, Bayan; Alissa, Khalid; Alakrawi, Zahra; Alumran, Arwa
Background: The digital revolution has had a huge impact on healthcare around the world. Digital technology could dramatically improve the accuracy of diagnosis, treatment, health outcomes, efficiency of care, and workflow of healthcare operations. Using health information technology will bring major improvements in patient outcomes. Purpose: This study aims to measure the readiness for digital health transformation at different hospitals in the Eastern Province, Saudi Arabia in relation to Saudi Vision 2030 based on the four dimensions adopted by the Healthcare Information and Management Systems Society: person-enabled health, predictive analytics, governance and workforce, and interoperability. Methods: The study was conducted with a cross-sectional design using data collected through an online questionnaire from 10 healthcare settings, the questionnaire consists of the four digital health indicators. The survey was developed by Healthcare Information and Management Systems Society for the purpose of assessing the level of digital maturity in healthcare settings. Results: Ten healthcare facilities in the Eastern Province, both private and governmental, were included in the study. The highest total scores for digital health transformation were reported in private healthcare facilities (median score for private facilities = 77, public facilities = 71). The 'governance and workforce' was the most implemented dimension among the healthcare facilities in the study (median = 80), while the dimension that was least frequently implemented was predictive analytics (median score = 70). In addition, tertiary hospitals scored the least in digital transformation readiness (median = 74) compared to primary and secondary healthcare facilities in the study. Conclusion: The results of the study show that private healthcare facilities scored higher in digital health transformation indicators. These results will be useful for promoting policymakers' understanding of the level of digital health transformation in the Eastern Province and for the creation of a strategic action plan.